PENGARUH KONSENTRASI DAN INTERVAL WAKTU PEMBERIAN POC TERHADAP PERTUMBUHAN DAN HASIL TANAMAN BAWANG MERAH (Allium ascalonicum L.) - nurma wahidiyah (AGRONISMA, 2021)
This research aims to find out growth and yield of shallots due to different concentrations and intervals of POC of fish offal, banana hump and rabbit urine. The design used is factorial RAK with control, the first factor is the type of concentration ( K1 = 15/100 ml of water, K2 = 30/100 ml of water, K3 = 45/100 ml of water) and the second factor is the time interval (I1 = every 7 days interval and I2 = every 14 days interval) and controls. The results of the study show POC administration of fish offal, banana weevil and rabbit urine on concentration and time intervals gave a good effect on plant growth in K1I2 treatment but was not significantly different from other treatments on plant length parameters, leaf area, and number of leaves. The administration of POC concentration showed that the K1 treatment showed good treatment but was not significantly different from the K2 treatment on the parameters of plant length, number of leaves, leaf area, and number of tubers where the number of tubers was equal to1 ton/ha. While giving a good time interval tends to treatment I2 parameters of plant length, number of leaves, and number of dry bulbs per clump.